Experimental and theoretical investigation of the reaction of RO2 radicals with OH radicals: Dependence of the HO2 yield on the size of the alkyl group. Issue 9 (25th June 2018) - Assaf, Emmanuel; Schoemaecker, Coralie; Vereecken, Luc; Fittschen, Christa
Abstract: The HO2 yield in the reaction of peroxy radicals with OH radicals has been determined experimentally at 50 Torr helium by measuring simultaneously OH and HO2 concentration time profiles, following the photolysis of XeF2 in the presence of different hydrocarbons and O2 . The following yields have been obtained: ϕ CH 3 O 2  = (0.90 ± 0.1), ϕ C 2 H 5 O 2  = (0.75 ± 0.15), ϕ C 3 H 7 O 2  = (0.41 ± 0.08), and ϕ C 4 H 9 O 2  = (0.15 ± 0.03). The clear decrease in HO2 yield with increasing size of the alkyl moiety can be explained by an increased stabilization of the trioxide adduct, ROOOH. This has been confirmed by ab initio and Rice–Ramsperger–Kassel–Marcus master equation calculations. Extrapolation of the experimental results to atmospheric conditions shows that the stabilized adduct, ROOOH, is the nearly exclusive product of the reaction between OH radicals and peroxy radicals containing more than three C‐atoms. The fate and possible impact of these species is completely unexplored so far.